1966
DOI: 10.1128/jb.92.1.107-115.1966
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inducible Liver Enzymes by Endotoxin and Actinomycin D

Abstract: Inhibition of inducible liver enzymes by endotoxin and actinomycin D. J. Bacteriol. 92:107-115. 1966.-Bacterial endotoxin at the LD50 level lowers liver tryptophan pyrrolase in mice, it prevents for 16 to 20 hr the induction of the enzyme by a concurrent injection of cortisone, it lowers significantly but does not prevent substrate induction, and it reduces the enzymatic activity promptly and significantly when administered during the course of hormonal induction. The LD50 amount of actinomycin D has a similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0

Year Published

1967
1967
1983
1983

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
5
13
0
Order By: Relevance
“…The investigation of changes in host enzyme activity after infection with S. typhimurium did not confirm prior studies on TO which showed an inhibition of this enzyme after injection of endotoxin (3,4). But the observed increases in TAT and PK are compatible with reported data (5,17).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The investigation of changes in host enzyme activity after infection with S. typhimurium did not confirm prior studies on TO which showed an inhibition of this enzyme after injection of endotoxin (3,4). But the observed increases in TAT and PK are compatible with reported data (5,17).…”
Section: Discussionsupporting
confidence: 92%
“…The increase in activity of TAT during infection with S. typhimurium is consistent with published work on the effect of endotoxin on this enzyme (5). The increase in PK activity observed during infection is compatible with other work from our laboratory which shows an increase in PK activity after endotoxin injection (17).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Endotoxin inhibits PEPCK, therefore, in a fashion similar to that of actinomycin D, but different from puromycin. The similarity of action of endotoxin and actinomcyin D on the induction of hepatic enzymes was first pointed out by Berry et al (1). It was reported by these investigators that actinomycin D and the bacterial poison yielded identical results in inhibiting the induction of the enzyme tryptophan oxygenase in animals that received 5 mg of cortisone acetate.…”
Section: Methodsmentioning
confidence: 92%
“…The hormonal induction of two enzymes, tryptophan oxygenase and phosphoenolpyruvate carboxykinase, is strongly inhibited by endotoxin, whereas the third enzyme, tyrosine-a-ketoglutarate transaminase, is not inhibited. In intact mice, this enzyme is induced by endotoxin to approximately the same degree as it is by hormone, whereas only a limited but statistically significant induction occurs in adrenalectomized mice (5). The contrast in response of these three enzymes establishes the fact that endotoxin is not exerting its anti-inductive effect through general hepatotoxicity but, on the other hand, appears to have a selective action on certain enzymes.…”
mentioning
confidence: 91%